Prevalence and predictors of risky and heavy alcohol consumption among adult siblings of childhood cancer survivors. Issue 5 (27th June 2012) - Lown, E. Anne; Mertens, Ann C.; Korcha, Rachael A.; Leisenring, Wendy; Hudson, Melissa M.; Greenfield, Thomas K.; Robison, Leslie L.; Zeltzer, Lonnie K.
Abstract Objective To describe alcohol consumption patterns and risk factors for risky and heavy alcohol use among siblings of childhood cancer survivors compared with survivors and national controls. Methods Secondary analysis of prospectively collected data from two national surveys was performed including a cohort of 3034 adult siblings of childhood cancer survivors (age 18–56 years) and 10, 398 adult childhood cancer survivors, both from the Childhood Cancer Survivor Study, plus 5712 adult participants from the population‐based National Alcohol Survey. Cancer‐related experiences, self‐reported current health, and mental health were examined in relation to alcohol consumption patterns including heavy and risky drinking. Results Adult siblings of childhood cancer survivors were more likely to be heavy drinkers (ORadj = 1.3; 1.0–1.6) and risky drinkers (ORadj = 1.3; 1.1–1.6) compared with controls from a national sample. Siblings were also more likely to drink at these two levels compared with survivors. Factors associated with heavy drinking among siblings included being 18–21 years old (ORadj = 2.9; 2.0–4.4), male (ORadj = 2.3; 1.7–3.0), having a high school education or less (ORadj = 2.4; 1.7–3.5), and drinking initiation at a young age (ORadj = 5.1; 2.5–10.3). Symptoms of depression, (ORadj = 2.1; 1.3–3.2), anxiety (ORadj = 1.9; 1.1–3.3), and global psychiatric distress (ORadj = 2.5; 1.5–4.3) were significantly associated with heavy alcohol use. Conclusions Siblings of children with cancer are more likely to be risky and heavy drinkers as adults compared with childhood cancer survivors or national controls. Early initiation of drinking and symptoms of psychological distress should be identified during early adolescence and effective sibling‐specific interventions should be developed and made available for siblings of children with cancer. Copyright © 2012 John Wiley & Sons, Ltd.